Combination of contracts in Islamic Finance practices in the light of Hadith on prohibition of ‘Two Contracts in One Contract’ (Bay’atan fi Bay’ah): a Shari’ah investigation - Habibur Rahman, Muhammad; Osmani, Noor Mohammad (UNIPSAS, Pahang, 2022)
To cater the dramatic changes in market demands, Islamic financial institutions supply various types of Islamic financial products and services. Some of them are categorized as a hybrid in nature, which combines more than one contract. Essentially this would be assumed to trigger the shari’ah compliant issue because, in more than one narration, the Prophet (SW) prohibits the combination of two contracts in a single agreement. As reported in many sources, the Prophet (SW) prohibited two sales in one sale (bay’atan fi bay’ah) and two agreements in one agreement (safqatan fi safqah). Also, he prohibited the combination of sale and loan contracts (bay’ wa salaf) in a single arrangement. Thus, this study investigates the shari’ah status of Islamic financial hybrid products in light of these prophetic narrations. This study is qualitative, and a method of document analysis, both classical and contemporary, has been followed to achieve the study's objective. The study concludes that the combination of more than one contract in a single arrangement is not prohibited in general; it shall be subject to the nature and essence of the contracts instead. A combination of partnership with the lease contract is not prohibited as both contracts are not inconsistent with each other. While a combination of a loan contract with another contract that begets benefit for the loan is not permissible as such combination converts the arrangement into a usurious transaction.